2021
DOI: 10.3389/fmed.2021.769208
|View full text |Cite
|
Sign up to set email alerts
|

Did Climate Change Influence the Emergence, Transmission, and Expression of the COVID-19 Pandemic?

Abstract: The human race has survived many epidemics and pandemics that have emerged and reemerged throughout history. The novel coronavirus Severe Acute Respiratory Syndrome SARS-CoV-2/COVID-19 is the latest pandemic and this has caused major health and socioeconomic problems in almost all communities of the world. The origin of the virus is still in dispute but most likely, the virus emerged from the bats and also may involve an intermediate host before affecting humans. Several other factors also may have affected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 126 publications
(168 reference statements)
0
17
0
Order By: Relevance
“…Long-term stress-related chronic inflammations is also linked with higher risk for several diseases such as cardiovascular disease, cancers, diabetes, and autoimmune diseases ( Dhabhar, 2014 ; Furman et al, 2019 ; Liu et al, 2017 ). Several reports have shown that the presence of underlying comorbidities such as cerebrovascular diseases, chronic lung diseases, cancer, diabetes, and hypertension could increase the incidence and severity of SARS COV-2 infection ( Callender et al, 2020 ; Ejaz et al, 2020 ; Gupta et al, 2021 ; Honardoost et al, 2021 ). With current day lifestyle, incidences of diabetes, hypertension, and mental health-related diseases are increasing in young adults ( Asif, 2014 ; Di Renzo et al, 2020 ; C. Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term stress-related chronic inflammations is also linked with higher risk for several diseases such as cardiovascular disease, cancers, diabetes, and autoimmune diseases ( Dhabhar, 2014 ; Furman et al, 2019 ; Liu et al, 2017 ). Several reports have shown that the presence of underlying comorbidities such as cerebrovascular diseases, chronic lung diseases, cancer, diabetes, and hypertension could increase the incidence and severity of SARS COV-2 infection ( Callender et al, 2020 ; Ejaz et al, 2020 ; Gupta et al, 2021 ; Honardoost et al, 2021 ). With current day lifestyle, incidences of diabetes, hypertension, and mental health-related diseases are increasing in young adults ( Asif, 2014 ; Di Renzo et al, 2020 ; C. Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bats also have significant quantities of heat shock proteins, which defend them against high temperatures and oxidative stress by chaperoning viral proteins and giving the ability to cause virus mutations. Another noteworthy anti-microbial function is mediated by their gut flora, which produces compounds that aid in the formation of their immunological defences" [45].…”
Section: Respiratory Zoonosesmentioning
confidence: 99%
“…A variety of meteorological conditions may have contributed to the propagation of the virus during the COVID-19 pandemic, but more study is needed to understand how these processes function [45].…”
Section: Respiratory Zoonosesmentioning
confidence: 99%
“…It also increases the spread of diseases, emerging infectious diseases, and pandemics. (2,3) The scientific community focuses research on CO2 concentrations more than other greenhouse gases due to the gas abundance in the atmosphere. It is also the main contributor to climate change.…”
Section: Introductionmentioning
confidence: 99%